Parallax in “Pi of the Sky” project - Majcher, A; Sokolowski, Marcin; Batsch, T; Castro-Tirado, A; Czyrkowski, H; Cwiek, A; Cwiok, M; Dabrowski, R; Kasprowicz, G; Majczyna, A; Malek, K; Mankiewicz, L; et al. (Elsevier Ltd, 2013)
The main goal of the “Pi of the Sky” project is search for optical transients (OTs) of astrophysical origin, in particular those related to gamma-ray bursts (GRBs). Since March 2011 the project has two running observatories: one in northern Chile and the other one insouthern Spain. This allows for regular observations of a common sky fields, visible from both observatories which are scheduled usually 1–2 h per night. In such a case, the on-line flash recognition algorithm, looking for optical transients, can use parallax information toassure that events observed from both sites have parallax angle smaller than the error of astrometry. On the other hand, the remaining OT candidates can be verified against a hypothesis of being near-Earth objects. This paper presents algorithm using parallax information for identification of near-Earth objects, which might be satellites, or space debris elements. Preliminary results of the algorithm are also presented.